Transatlantic fascism : ideology, violence, and the sacred in Argentina and Italy, 1919-1945 - Finchelstein, Federico, 1975- (e-Duke books scholarly collection., 2010)
This history of the connections between Argentine and Italian fascisms explains how Italy promoted fascism in Argentina, and how far-right Argentines adopted some elements of Italian fascism and rejected others.